A Study of the Concepts of Waste in the Textbooks of Sciences - Alaa Ahmed Abdulwahed, Ali Hussein Hasan Al-Naily, Mazin Thamer Shnaef, (Opción, 2019)
This study aims at investigating the inclusion of the concept of waste in the contents of textbooks of sciences of the primary stage for the academic year 2018-2019 via comparative quantitative research methods. As a result, the sciences textbook of the fourth grade of the primary stage has got the first place in devoting attention to the concepts of waste, while the third and fifth grades have got the second place. In conclusion, textbooks of sciences of the primary stage have paid very weak attention to the concepts of waste in comparison with the default ratio.